Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1988
DOI: 10.1002/jmv.1890260309
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of hospital‐acquired rotavirus gastroenteritis using RNA electrophoresis

Abstract: Rotavirus is a common cause of diarrhoea both in the community and in the hospital. Because of this, it may be difficult to determine whether crossinfection has occurred in the hospital, an important finding as review of hygienic techniques and ward closure may be indicated. We therefore investigated the use of Polyacrylamide gel electrophoresis (PAGE) of the rotavirus RNA genome as a means of distinguishing between rotavirus strains in order to assess its role in the evaluation of apparent hospital-acquired r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
(5 reference statements)
0
6
0
Order By: Relevance
“…20 Clinical infection occurs in adults with exposure to as little as 10 4 or 10 5 particles. 27 Most infections result from contact with infected persons, primarily by fecal to oral route. 12 Transmission can occur for 2 days before symptomatic gastroenteritis and for nearly 2 weeks after clinical illness is apparent.…”
Section: Pathogenesis and Epidemiologymentioning
confidence: 99%
“…20 Clinical infection occurs in adults with exposure to as little as 10 4 or 10 5 particles. 27 Most infections result from contact with infected persons, primarily by fecal to oral route. 12 Transmission can occur for 2 days before symptomatic gastroenteritis and for nearly 2 weeks after clinical illness is apparent.…”
Section: Pathogenesis and Epidemiologymentioning
confidence: 99%
“…We identified 17 studies [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] on outbreaks involving C. difficile, norovirus, rotavirus, Salmonella panama, small round structured virus, or small round structured virus and small round featureless virus. The primary mode of transmission for all these pathogens is direct person-to-person contact and indirect contact with contaminated surfaces [20].…”
Section: Gastrointestinal System (Table 1)mentioning
confidence: 99%
“…The definition of ward closure varied across the studies, and ward closure lasted between 3 days and 1 month among the studies that reported length of closure. Six studies defined ward closure as prohibiting new admissions to the affected clinical area (i.e., unit/ward/bay) [21][22][23][24][25][26]. Widdowson and colleagues reported on a study that utilized a phased approach, first halting new admissions and discharging all cases, then halting all admissions and discharging all patients from the area [27].…”
Section: Gastrointestinal System (Table 1)mentioning
confidence: 99%
See 1 more Smart Citation
“…Sadly this technique was not available universally, but at QEHC it was a vital diagnostic technique because of the clinical frequency of acute gastroenteritis in the local population of children from East London. 22 The most dramatic advances for accurate diagnosis and clinical research concerning diseases of the small intestine, however, came from the widespread use of small intestinal suction biopsy using variations of the paediatric Crosby capsule. This transformed the accurate diagnosis and understanding of small intestinal diseases.…”
Section: Technological Advances In Diagnosismentioning
confidence: 99%